THE “NICOLAITA” (MICHOACANA) UNIVERSITY REFORM 1971-1986 (Tzintzun, Revista de Estudios Históricos, 2016)
This paper analyzes the academic, administrative and regulatory transformationprocess which took place in the Michoacana University from 1971 to 1986 under themodernizing project of higher education implemented by the President LuisEcheverría Álvarez and maintained, with certain variables, by the following presidentsJosé Lopez Portillo and Miguel De La Madrid Hurtado. The purpose of thatproject was to modernize the University in order to adapt it to the demands of thenew stage of the economical development of the country and to make it the engine ofthe industrial development by forming the necessary human resources. The projectimplied to overpass the traditional university schema and to structure the curriculakeeping in mind the production needs. In order to do that, the Federal Government,through the ANUIES, adopted the departmental model used in the United States.The Michoacana University received the necessary money to put it into practice.However, the American model crashed against the university traditional structure.Therefore, it was difficult to change.
Keywords: Michoacana (Nicolaita) University; University History; Educative Modernization; University Departments; Luis Echeverría Álvarez